Pavlenko, A. P. Czechoslovak Corps and the Russian Civil War (Regional Aspect). Review of: Vasilchenko, M. A. (2021). Chekhoslovatskii korpus v bor’be za Povolzh’e (mai — noiabr’ 1918 goda) [Czechoslovak Corps in the Struggle for the Volga Region (May — November 1918)]. Saratov: Tekhno-Dekor. 172 p. - Aleksey Pavlovich Pavlenko (Известия Уральского федерального университета. Серия 2: Гуманитарные науки)
This work reviews M. A. Vasilchenko’s monograph devoted to the Volga group of the Czechoslovak Corps as a participant in the Civil War in Russia. This book examines both regional and all-Russian plots of the history of Czechoslovak military units in Russia in 1918. The review summarises the historiography of the uprising of Czech and Slovak legionnaires, the results of M. A. Vasilchenko’s work fit into the historiographical context. It is noted that the author of the reviewed monograph focuses on the study of internal processes that led to the uprising of the Czechoslovak corps against the Bolsheviks. M. A. Vasilchenko’s work belongs to the historiographical direction, which believes that the uprising of the Czechoslovaks was originally aimed only at preserving the corps as a combat unit and providing an opportunity to evacuate from Russia. And only afterwards was the Czechoslovak Corps drawn into the Civil War on the side of the anti-Bolshevik forces. The key factor that led to the rebellion, according to M. A. Vasilchenko, was the process of autonomisation — the gradual separation of the corps units from the Russian army and the Russian state. The review notes that M. A. Vasilchenko pays insufficient attention to the consideration of external factors that could influence the performance of the Czechoslovaks.